The Shepherd of Hermas a literary, historical, and theological handbook - Lookadoo, Jonathon 1987- (London Bloomsbury Publishing Plc, 2021)
Cover -- Half Title -- Title -- Copyright -- Dedication -- Contents -- Acknowledgments -- Abbreviations -- Introduction -- Part I Introducing the Shepherd of Hermas -- Chapter 1 An Overview of the Shepherd -- Chapter 2 How Was the Shepherd Preserved? -- Chapter 3 Who Read the Shepherd? -- Chapter 4 Critical Questions for the Shepherd: What, to Whom, Where, When, and Who? -- Part II Studying the Shepherd of Hermas -- Chapter 5 Fasting and the Vineyard: Exegeting Similitude 5 -- Chapter 6 The Characters in the Shepherd -- Chapter 7 The Shepherd in Its Greco-Roman and Early Jewish Settings -- Chapter 8 The Shepherd and Early Christian Literature in the First Two Centuries -- Chapter 9 God in the Shepherd -- Chapter 10 Sin and Repentance -- Chapter 11 Metaphors and Imagery in the Shepherd: The Tower and the House -- Chapter 12 Spirit Language in Mandates 5-11: From Ancient Philosophy to Contemporary Theology -- Bibliography -- Index of Authors -- Index of References -- Index of Subjects.
Description based on publisher supplied metadata and other sources
Keywords: English literature; Electronic books